Ethno-Cultural Values – Basics of Turning into Personality - Katinienė, Albina (Acta Paedagogica Vilnensia, 2003)
The article treats the Lithuanian ethno-culture consequence upon preschool child’s personality development. It has been proved by scientists long time ago, that person’s quality essentially depends upon cultural surroundings of a child. More democracy in our society, formation of social hardships, more and more aggressive multi-culture, merge of culture and illiteracy makes very dangerous situation in terms of a child’s morale, who still lacks criteria of values choice. Ethno-culture can do its best in protecting a person from negative influence. Scientists have proved, ethno-culture being essential in forming person’s structure, which is specific to each nation’s representative. While fostering a personality this structure becomes a gauge. Based on the above mentions propositions, the article presents the ethno-cultural pattern of preschool children education. It discusses ethno-cultural values appropriate to this particular age group, emphasizing its educational function. There are also singled out the main factors of education, their importance and activity brands of a child, which are supposed to impart ethno-cultural values. Examinations provide conclusion that ethno-culture can optimize the whole child’s personality development.